Sweat sodium and chloride contents in 8-14 years old children (A preliminary study) - I. Boediman; Dwi P. Widodo; Noenoeng Rahajoe (Paediatrica Indonesiana, 2018)
A modified Shwachman sweat test was performed on 152 children aged between 8-14 .4 years old, consisting of 54 girls (35.5%) and 98 boys (64%), to look for sweat electrolyte values. Mean sweat electrolyte contents in boys was higher than in girls. The mean sweat Na+ and Cl- were 50.15 ±25.83 mEq/L and 43 .76  m.Eq/l ± 24.67 respectively. The sweat electrolyte contents were not influenced by age.